Failure of Hip Reconstruction in Children With Cerebral Palsy: What Are the Risk Factors?. Issue 1 (January 2022) - Minaie, Arya; Gordon, J. Eric; Schoenecker, Perry; Hosseinzadeh, Pooya
Abstract : Background: The rates and risk factors contributing to failure after hip reconstruction among patients with cerebral palsy (CP) are not well established. In analyzing a large cohort of children with CP who underwent hip reconstruction, the objectives of this study are to establish (1) the failure rates and (2) associated risk factors. Methods: This retrospective study included chart and radiographic review of patients between the ages of 1 to 18, with a diagnosis of CP, who underwent a hip reconstructive procedure at a single children's hospital over a 9-year period (2010 to 2018). Patients without at least 2 years of follow-up were excluded. Age at time of surgery, sex, Gross Motor Function Classification System (GMFCS), procedure(s) performed, preoperative migration percentage (MP), neck-shaft angle, and acetabular index (AI) were recorded. Failure was defined as need for revision surgery or a MP >50% on follow-up radiographs. Logistic regression and multiple-variable regression-type models were used to test for significance of risk factors. Results: Of the 291 hips in 179 patients (102 males, 77 females) that met inclusion criteria, 38 hips (13%) failed. Significant differences in the failure group were seen in age at time of surgery (6.2±3.2 vs. 8.1±3.2; P <0.001), preoperative MP (62.3±28.7 vs. 39.9±24.1%; P <0.001) and preoperative neck-shaft angle (164.9±8.2 vs. 157.3±15.6 degrees; P <0.001). Age below 6 at time of surgery significantly increased failure rate (26% vs. 6.3%, P <0.001) as did preoperative MP >70% (28.9% vs. 9.9%, P <0.001). Receiving an acetabular osteotomy was protective against failure (9.1% vs. 16.9%, P =0.048), particularly in patients with a preoperative AI >25° (odds ratio=0.236; confidence interval: 0.090-0.549). Conclusions: In this case series, failure after hip reconstruction for children with CP was determined to be 13.1%. There was a higher risk associated with age under 6 at time of surgery or a preoperative MP >70%. Correction of acetabular dysplasia when AI is more than 25 degrees with acetabular osteotomy at time of hip reconstruction, exerted a protective effect against subsequent failure. Level of Evidence: Level III—retrospective case series.